The Role of Talent Management Comparing Medium-Sized and Large Companies – Major Challenges in Attracting and Retaining Talented Employees - Boštjančič, Eva; Slana, Zala (Frontiers in Psychology, 2018)
In order for companies to realize their organizational visions, they need staff who are high-potential and looking toward the future. Due to the demographic, social and economic situation in Europe, the labor market is already reflecting a lack of high-quality human resources (HR), which inspires research into and planned management of high-potential, i.e., talented, employees. Companies are aware that only those organizations that recognize this area as crucial and invest resources into it will be successful in the “war for talent.” The purpose of the study was to research the field of talent management from the perspective of the definition of what the talent management process means for companies, how to attract and recognize talented employees, what development activities to provide them with and how to measure their performance and progress. We employed an exploratory approach, using the method of semi-structured interviews to gather information from 21 HR professionals who work at medium-sized and large Slovenian companies. We found that these organizations use various approaches and activities to attract and develop talented employees. At two thirds of the companies, performance is measured using annual evaluation interviews, by measuring the meeting of targets and evaluations by superiors. The biggest challenges in the field are attracting talented employees and positioning the organization as a desirable employer. The study is useful primarily as an overview of the field and of best practices, which companies can use to argument their existing processes.